Neurofibromatosis type 1 or Von Recklinghausen's disease. A case report - Marisleidy Denis Rodríguez; Miguel Alejandro Pulido Gutiérrez; Thaimi Conde Cueto; Luis Omar López Hurtado (Medisur)
Neurofibromatosis type I or Von Recklinghausen's disease is one of the genetic diseases that affect the nervous system, named for its common embryonic origin. It is an autosomal dominant, progressive disease with an unpredictable course that affects the skin and the central and peripheral nervous system. The case of a seven-year-old female schoolchild who was admitted to the Paquito Gonzáles Cueto Pediatric Hospital due to the presence of several "coffee-with-milk" spots on her skin is presented. The presence of type 1 neurofibromatosis in her maternal grandmother and great-grandmother, the latter already deceased from said cause, was collected as a family history. On physical examination, Lisch nodules were found in the thickness of the iris of the left eye. Imaging studies revealed several hyperintense nodular lesions on T2 and FLAIR, at the level of the internal and external bilateral and left ventricular capsule, the largest measuring 20 x 11 mm, as well as a hypointense image at the level of the left optic nerve, measuring 7 mm. It was diagnosed as neurofibromatosis type I. Because it is one of the least studied diseases in our environment, it was decided to publish this case.